(untitled) (Universal International Scientific Journal, 2026)
: This scientific article analyzes the impact of the globalization process on the development of society and its socio-pedagogical characteristics. The impact of globalization on the education system, youth education, cultural values, and the activities of social institutions is scientifically covered. It also discusses new areas of pedagogical activity in the context of globalization, problems that arise in the process of socialization of youth, and ways to overcome them.